Early stage E-diagnosis of neurodegenerative diseases using label-free sensing of taurine biomarker by superconductive silver nano-ink: A miniaturized electro-device towards rapid neuro-analysis - Rokhsareh Ebrahimi; Nasrin Shadjou; Mohammad Hasanzadeh; Farnaz Bahavarnia (Sensors and Actuators Reports)
In this research, a novel paper-based sensor was developed for the label-free sensing of taurine biomarker in human plasma sample. Silver superconductive nano-ink was used for construction of electrochemical device which show high conductivity (about 1800 µA). Sensor fabrication process was characterized by FESEM, EDAX, and AFM methods. The modified electrode was utilized as transducer for sensitive and selective detection of Taurine biomarker by cyclic voltammetry, square wave voltammetry, and differential pulse voltammetry techniques. The engineered sensor exhibited suitable sensitivity and specificity for detecting taurine with a linear range of 10 to 500 µM and a lower limit of quantification of 10 µM. The engineered low-cost device shows great potential for the in-situ biomedical analysis of neurodegenerative diseases using e-diagnosis technology.